Analisis kinerja keuangan bank seabank: kajian deskriptif terhadap roa dan npl dalam 5 tahun terakhir - Afrizal, Nova Maulana (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the financial performance of Seabank Bank by focusing on two main indicators, namely Return on Assets (ROA) and Non-Performing Loans (NPL) for the last five years. ROA is used to measure the bank's efficiency in managing its assets to generate income, while NPL reflects the credit quality and risks faced by the bank. The analysis shows that fluctuations in Seabank's ROA and NPL are strongly influenced by economic conditions and the risk management applied. In 2019, NPLs were recorded high at 7.63%, potentially reducing customer confidence. However, in 2021, NPLs decreased dramatically to 1.35%, indicating a significant improvement in credit quality. Meanwhile, a stable ROA is an important indicator in attracting stakeholder confidence. This research provides insights into the importance of asset and risk management in improving the financial performance of banks, as well as implications for future management strategies. Thus, this study is expected to serve as a reference for financial institutions in improving competitiveness and customer trust.